Means of Amusement and Recreation of Urban Life in Punjab under the Sultan of Delhi: The Influence of the Delhi Sultanate on Urban Amusement and Recreation in Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2013)
With the establishment of Delhi Sultanate, the remarkable changes occurred in the various sources of pleasure and recreation, especially in urban life. The Turks were settled in the urban centers so these changes seem to have occurred in the life of urban elite. The amusements and pleasures of the age were strongly influenced by its military characteristics. Military exercise began to occupy a sacred place in their routine life. People used to carry swords like walking sticks and made skilful use of them when occasions arose.[1] The one aspect of the social life of this period was razam or warfare and bazmi or social pleasures which were complementary to one another. Every man was expected to be an active soldier capable of doing military duty in times of war. The people of the Punjab always had to endure the most of the invaders. But during the time of peace, they indulged in pleasure, pastime and recreative sports.[2] The Turks brought the new means of recreations and amusements. The games like chaugan (polo), Shikar and animal fights etc. were the monopoly of the aristocratic and ruling class of the urban milieu of the Punjab while the chess, chaupar, playing card, etc, were popular among the rich and poor alike.[3]